2022
DOI: 10.1021/acs.jcim.1c01223
|View full text |Cite
|
Sign up to set email alerts
|

Computational Identification of Possible Allosteric Sites and Modulators of the SARS-CoV-2 Main Protease

Abstract: In this study, we target the main protease (Mpro) of the SARS-CoV-2 virus as it is a crucial enzyme for viral replication. Herein, we report three plausible allosteric sites on Mpro that can expand structure-based drug discovery efforts for new Mpro inhibitors. To find these sites, we used mixed-solvent molecular dynamics (MixMD) simulations, an efficient computational protocol that finds binding hotspots through mapping the surface of unbound proteins with 5% cosolvents in water. We have used normal mode anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…These studies revealed sites other than the catalytic active sites with favorable free energies of binding that overlapped the values obtained by docking the same ligands into the active sites. Furthermore, these results were in agreement with recent reports of allosteric binding sites in Mpro [ 34 , 35 ]. Because allosteric sites have been less explored than catalytic sites and allosteric binding could furnish new avenues for modulating the activity of Mpro [ 36 ], discovery of allosteric binding sites was incorporated into the present work.…”
Section: Introductionsupporting
confidence: 93%
“…These studies revealed sites other than the catalytic active sites with favorable free energies of binding that overlapped the values obtained by docking the same ligands into the active sites. Furthermore, these results were in agreement with recent reports of allosteric binding sites in Mpro [ 34 , 35 ]. Because allosteric sites have been less explored than catalytic sites and allosteric binding could furnish new avenues for modulating the activity of Mpro [ 36 ], discovery of allosteric binding sites was incorporated into the present work.…”
Section: Introductionsupporting
confidence: 93%
“…However, in our work, we also report on a residue community analysis of the enzyme, which notably suggested that CCG‐50014 disrupted inter‐community correlations stemming for the catalytic residues C145 and H41. These observations highlight the role of allostery in this enzyme, which could prove useful in designing potential therapeutics targeting the enzyme via an allosteric mechanism 75–77 …”
Section: Resultsmentioning
confidence: 90%
“…These observations highlight the role of allostery in this enzyme, which could prove useful in designing potential therapeutics targeting the enzyme via an allosteric mechanism. 75 , 76 , 77 …”
Section: Resultsmentioning
confidence: 99%
“…Encouragingly, following the very recent surge of research around the M pro of SARS-CoV-2, some experimental studies have found drugs and small fragments that bind to sites other than the substrate binding site on this protein, and that might have implications for allosteric regulation [29] , [30] . Preliminary studies have also simulated binding events to distant areas of the protein by using docking and molecular dynamics (MD) [31] , [32] , [33] , MD [34] , [35] , [36] , [37] , [38] or elastic network models (ENMs) [39] , [40] . Moreover, there have already been indications of allosteric processes mediated by the extra domain in the protease of the old SARS-CoV [41] , [42] , [43] , [15] .…”
Section: Introductionmentioning
confidence: 99%